The Paradoxical Corporate and Securities Law Implications of Counsel Serving on the Client's Board - James D. Cox (Washington University Law Quarterly, 2002)
This Article assumes that dual service will continue to be a practice, but not because it is the socially optimal result. Rather, dual service will continue to exist because it is, and has been, sufficiently pervasive to provide cause to believe no jarring change, such as proscription by the American Bar Association (ABA) or state bar organization, is even likely to occur. This Article provides a new perspective on the topic by examining the junction of a lawyer serving on his client’s board and well-accepted corporate and securities principles. While this inquiry should strike many as natural, the conclusions reached within this Article are paradoxical. As examined below, dual service has the effect of increasing the protection accorded the beneficiaries of the examined corporate and securities law principles. The paradox lies in the fact that the invitation to serve comes from a firm’s managers and the examined principles are those crafted with a special objective of protecting shareholders and investors, even the corporation, from misconduct by the managers. As demonostrated in this Article, dual service results in managers being subject to greater scrutiny and lawyers to a loss of some of the client’s business. Further, dual service even makes it possible for a competing lawyer to get his foot into the client’s door, a result that an attorney who agrees to serve on his client’s board certainly does not seek. Hence, why the invitation? And why the acceptance of the offer to serve on the client’s board?
Keywords: Corporate lawyers; Executives; Legal ethics; Securities fraud; Boards of directors; Corporation law